Waiting for QUIC : on the opportunities of passive measurements to understand QUIC deployments - Jonas Mücke and Marcin Nawrocki and Raphael Hiesgen and Patrick Sattler and Johannes Zirngibl and Georg Carle and Thomas C. Schmidt and Matthias Wählisch (De.arxiv.org, 2022)
In this paper, we study the potentials of passive measurements to gain advanced knowledge about QUIC deployments. By analyzing one month backscatter traffic of the /9 CAIDA network telescope, we are able to make the following observations. First, we can identify different off-net deployments of hypergiants, using packet features such as QUIC source connection IDs (SCID), packet coalescence, and packet lengths. Second, Facebook and Google configure significantly different retransmission timeouts and maximum number of retransmissions. Third, SCIDs allow further insights into load balancer deployments such as number of servers per load balancer. We bolster our results by active measurements.